Groin hernias: causes, diagnostics, and surgery - V. I. Podoluzhnyi; S. M. Lesnikov; O. V. Shabalina (Фундаментальная и клиническая медицина)
Groin hernias occur in 27–48% of men and 3–6% of women during lifetime. Among the causes are inherited or age-related connective tissue or muscular dysplasia, lack of diverticular obliteration in fetal parietal peritoneum, pre-peritoneal lipomas migrating into the hernia ring, and congenital, postpartum, or postoperation dilation of the femoral ring. Physical examination and examination of the preperitoneal space reveals hernia in 93% and 100%, respectively, yet ultrasound examination, computed tomographic peritoneography, magnetic resonance imaging are also employed to confirm the diagnosis. An established technique for the treatment of groin hernias includes opening the inguinal canal, high ligation of the hernia sac, and repair of the inguinal canal, altogether termed herniorrhaphy. Suprapubic or inguinal incision permits closure of the hernia sac without involving the inguinal canal (herniotomy). Implementation of synthetic meshes led to the increase in hernioplasty, i.e. reinforcement of the inguinal canal upon the inguinal canal repair. Laparoscopic transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) hernioplasty became widely used along with the development of endoscopic surgery. In these techniques, mesh is placed between the peritoneum and transversalis fascia, closing both inguinal canal and femoral ring. Overall, modern surgical techniques reduced the time of treatment, disability and disease recurrence to 1.4–2%.